Capital structure and CEO tenure in microfinance institutions1. (24th August 2018) - Pascal Ndaki1, Daudi; Atle Beisland, Leif; Mersland, Roy
Abstract : There is a positive association between CEO tenure and the debt proportion of microfinance institutions. Microfinance institutions need improved access to debt capital to cover a huge and increasing world demand for microfinance services. More experienced CEOs may be more aligned with the microfinance institution's mission, and they may have a better understanding of the business model of microfinance. Moreover, capital providers may require a proven track record within the institution to supply funding.